Co-Fe-LDH / LDO double-doped modified carbon mixed cement-based material and preparation method and raw material ratio correction method thereof

By using double-doped Co-Fe-LDH/LDO modified materials in carbon-mixed cement, the problems of poor fluidity and low carbon dioxide absorption are solved, and the high flowability and high carbon sequestration capacity of the cement are achieved, which significantly improves its early and later strength.

CN119874280AActive Publication Date: 2025-04-25ZHEJIANG UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411971417.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-25
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

Existing carbon-mixed cements face the problems of poor liquidity and low carbon dioxide absorption, and the mixing of LDH and LDO rarely appear.

Method used

The modified carbon-mixed cement-based material with double doping of Co-Fe-LDH/LDO is used to improve the flowability and carbon sequestration ability of cement by controlling the incorporation ratio of LDH and LDO and the inflow of carbon dioxide.

Benefits of technology

The early and late strength of carbon mixed cement was significantly improved, and the flow was significantly enhanced. The early 3d strength reached 17.32Mpa, the late 28d strength reached 36.77Mpa, and the maximum flow was 30.04cm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874280A_ABST
    Figure CN119874280A_ABST
Patent Text Reader

Abstract

The invention provides a Co-Fe-LDH / LDO double-doped modified carbon mixed cement-based material as well as a preparation method and a raw material ratio correction method of the Co-Fe-LDH / LDO double-doped modified carbon mixed cement-based material. Raw materials of the Co-Fe-LDH / LDH composite material comprise cement, mixing water, Co-Fe-LDH, Co-Fe-LDO and carbon dioxide. The preparation method comprises the following steps: firstly, adding Co-Fe-LDH and Co-Fe-LDO into part of mixing water, and carrying out ultrasonic dispersion to obtain a uniformly dispersed mixed solution; and pouring cement into a stirring device, adding the mixed solution and the residual mixing water, continuously introducing carbon dioxide to a specified amount, and uniformly stirring to obtain the LDH / LDO modified carbon mixed cement-based material. The raw material ratio is regulated and controlled according to a calculation formula to obtain an optimal design ratio method of the cement fluidity and the carbon sequestration amount, so that the working performance and the carbon sequestration capacity of the cement are effectively ensured; the material effectively utilizes and absorbs carbon dioxide and slows down the greenhouse effect, and the prepared cement is high in carbon sequestration capacity and good in fluidity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of low-carbon concrete, and in particular to a modified carbon-mixed cement-based material doped with Co-Fe-LDH / LDO, a preparation method thereof, and a raw material ratio correction method. Background Art

[0002] Layered double hydroxide (LDH) is a composite metal hydroxide with a host-guest structure. The main body of the layer is composed of two or more metal cations, and the interlayer is anions and water molecules. It has excellent properties such as interlayer ion exchangeability, structural memory effect, thermal stability, acid-base dual functionality, etc., and is widely used in catalysts, lubricants, medical industries, etc.

[0003] The application of layered double hydroxides in cement-based materials is one of the hot topics in current research. Due to its excellent ion exchange and adsorption properties, it can be used to bind chloride ions and carbonate ions in cement-based materials, effectively reducing the carbonation effect and chloride ion erosion of mixed concrete. After calcination at above 600°C, LDH can obtain the calcined product LDO, which retains the layered structure of LDH and has a greatly increased specific surface area; therefore, its adsorption effect is significantly enhanced compared to LDH. In addition, LDO has adjustable surface acid-base properties and a two-dimensional layered structure, so it can also be used as an active multiphase catalyst and carrier. However, LDO has higher alkalinity than LDH, and due to the destruction of part of its interlayer structure caused by calcination, its ion binding ability will be reduced to a certain extent compared to LDH.

[0004] Compared with conventional calcium aluminum and magnesium aluminum based LDH, cobalt iron based LDH has higher current density and thermal stability. At the same time, its crystal interlayer spacing is larger, which helps to promote the binding and adsorption of ions. It also has a higher specific surface area, and its adsorption capacity can reach 2 to 3 times that of conventional LDH. Therefore, it is very advantageous to select cobalt iron based LDH as a modified material for carbon mixed cement.

[0005] The Chinese invention patent with patent number CN112745084A discloses a NiFe-LDH cement-based composite absorbing material and a preparation method thereof. By adding a uniformly dispersed NiFe-LDH mixed aqueous solution when mixing cement, a cement-based composite absorbing material with low electromagnetic wave reflectivity is obtained, which can effectively absorb electromagnetic wave pollution. The Chinese invention patent with patent number CN115784647A discloses a preparation process of modified cement and its early-strength ultra-high performance concrete, by dispersing Li-Fe layered double metal hydroxide powder and acidic retarder in ethanol liquid to form a mixed suspension. The atomized mixed suspension is collided with cement particles carried by hot carrier gas, so that the mixed suspension is sprayed onto the surface of cement particles, and the ethanol on the surface of cement particles is evaporated under the action of hot carrier gas to obtain modified cement, and the prepared concrete has the characteristics of ultra-early strength, setting time, and more stable early performance.

[0006] Most of the existing invention patents are about adding LDH to cement for mixing, thereby effectively improving its various properties, but the application of LDH and LDO mixed in carbon-mixed cement is rare, and the current carbon-mixed cement faces problems such as poor fluidity and low carbon dioxide absorption. Combining the advantages and disadvantages of LDH and LDO, it is possible to consider improving the working performance of carbon-mixed cement by the composite addition of LDH and LDO. Therefore, it is of great significance to develop a modified carbon-mixed cement material with good fluidity, i.e., fluidity, and high carbon dioxide absorption. Summary of the invention

[0007] The purpose of the present invention is to provide a modified carbon-mixed cement-based material doped with Co-Fe-LDH / LDO, a preparation method thereof, and a raw material ratio correction method. The material is simple to prepare and easy to use, can effectively improve the fluidity and carbon fixation capacity of carbon-mixed cement, and has a high application value in the field of low-carbon concrete. The raw material ratio correction formula mentioned in the present invention can effectively combine the ratio research and control the amount of carbon dioxide absorbed according to the required fluidity, which has a wide range of application prospects and a certain research reference value.

[0008] To achieve the above object, the present invention adopts the following technical solution:

[0009] A modified carbon mixed cement-based material doped with Co-Fe-LDH / LDO comprises the following components by weight: 350-400 parts of cement, 200-250 parts of mixing water, 3-4 parts of cobalt-iron layered double metal hydroxide Co-Fe-LDH, 2-3 parts of calcined cobalt-iron layered double metal hydroxide Co-Fe-LDO, and 2-8 parts of carbon dioxide;

[0010] Wherein, the calcined cobalt-iron layered double hydroxide Co-Fe-LDO is prepared by the following steps:

[0011] Step a1: Take some Co-Fe-LDH and calcine it at 600° C. in a muffle furnace with a heating rate of 3° C. / min. After keeping warm, cool it naturally to obtain calcined cobalt-iron layered double hydroxide Co-Fe-LDO.

[0012] Furthermore, the cement is ordinary Portland cement, and the model is P·O 42.5.

[0013] Furthermore, the particle size of the cobalt-iron layered double hydroxide Co-Fe-LDH is 0.5-2.0 microns, and the specific surface density is 0.2-0.4 g / mol.

[0014] A method for preparing a modified carbon-mixed cement-based material doped with Co-Fe-LDH / LDO, which is used to prepare any of the modified carbon-mixed cement-based materials doped with Co-Fe-LDH / LDO, comprising the following steps:

[0015] Step 1, weighing 100-120 parts of mixing water from the 200-250 parts of mixing water by mass, adding the Co-Fe-LDH and the Co-Fe-LDO to the weighed mixing water, and performing ultrasonic dispersion until the dispersion is uniform to obtain a milky white LDH / LDO suspension;

[0016] Step 2: Add the cement into a stirring device for dry mixing, then add the remaining mixing water and LDH / LDO suspension, and continue stirring until the mixture is uniform to obtain cement slurry;

[0017] Step 3, introducing the carbon dioxide into the cement paste at a rate of 8 to 10 L / min, and continuing to stir, so that the cement paste continuously absorbs carbon dioxide during the mixing process, and finally obtaining carbon-mixed cement paste;

[0018] Step 4: pour the carbon-mixed cement slurry into a mold, scrape off excess slurry, and demould after curing in a curing room for 7 days to obtain a modified carbon-mixed cement-based material doped with Co-Fe-LDH / LDO.

[0019] Furthermore, in step 1, the ultrasonic dispersion time is 60s-180s, in step 2, the dry mixing time is 30s, and the remaining mixing water and LDH / LDO suspension are continued to be stirred for 60s-120s.

[0020] Furthermore, during the curing process, the temperature is maintained at 20±2° C. and the relative humidity is maintained at above 95%.

[0021] Furthermore, the stirring device includes: a stirring tank, a stirring motor, a stirring element, a flow meter, a barometer, a buffer tank, a pressure cylinder, an A air pipe and a B air pipe; the stirring tank includes a stirring barrel and a stirring cover, the top of the stirring barrel is open for containing materials; the stirring cover is arranged at the top opening of the stirring barrel, and the stirring barrel is locked and sealed by a plurality of locks on the side of the stirring barrel; the stirring cover has a hole in the middle; the stirring element is arranged in the stirring tank, one end of which passes through the middle opening of the stirring cover and is fixedly connected to the output end of the stirring motor arranged on the upper end surface of the stirring cover; the barometer is used to detect the air pressure in the stirring tank; the pressure cylinder is connected to the buffer tank through the A air pipe; the buffer tank is used to convert the carbon dioxide released in the pressure cylinder into normal temperature and pressure, and pass the carbon dioxide into the stirring tank through the B air pipe; the flow meter is used to count the amount of carbon dioxide passed into the stirring tank.

[0022] Furthermore, one-way valves are provided on the A and B air pipes to prevent the reverse flow of carbon dioxide gas due to changes in air pressure; and rubber pads are provided on the contact surface between the stirring cover and the stirring barrel to improve the sealing effect.

[0023] A method for correcting the raw material ratio of a modified carbon mixed cement-based material doped with Co-Fe-LDH / LDO is used to correct the raw material ratio of the modified carbon mixed cement-based material doped with Co-Fe-LDH / LDO as described in any one of the above, characterized in that it comprises the following steps:

[0024] Step 1: Preliminary mix design of the water-cement ratio and the mass ratio of Co-Fe-LDH to Co-Fe-LDO m(LDH) / m(LDO) is performed according to the required carbon dioxide content;

[0025] Step 2: According to the Levenberg-Marquardt algorithm and the Spearman correlation coefficient algorithm, the carbon dioxide content is recorded as M1, m(LDH) / m(LDO) is recorded as M2, and the water-cement ratio is recorded as M3. M1, M2 and M3 are fitted with functions about the cement fluidity Y to obtain the following calculation formula:

[0026]

[0027] Step three, according to the required cement fluidity Y, according to the calculation formula obtained in step two, by changing the values ​​of M2 and M3 in the formula to adjust the maximum amount of carbon dioxide that can be adsorbed, and according to the values ​​of M2 and M3, the mix ratio in step one is corrected to obtain the final raw material mix ratio of modified carbon mixed cement-based materials.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] (1) The early and late strengths of the modified carbon mixed cement doped with LDH / LDO prepared by the present invention are significantly improved, and the fluidity is significantly enhanced; the early 3d strength reaches a maximum of 17.32Mpa, the late 28d strength reaches 36.77Mpa, and the fluidity reaches a maximum of 30.04cm.

[0030] (2) The present invention uses LDO, a calcined product of cobalt-iron layered double hydroxide, as a composite modified material, which is simple to prepare, stable in nature, and low in cost. In addition, the fluidity and carbon fixation capacity of carbon-mixed cement can be effectively changed by controlling the mixing ratio of Co-Fe-LDH and Co-Fe-LDO.

[0031] (3) The stirring device of the present invention can effectively control the amount of carbon dioxide introduced during the mixing process. The stirring speed is 2 to 4 times that of an ordinary cement mixing barrel, which can effectively promote the absorption of carbon dioxide by cement. In addition, the system is in a fully sealed state, which can ensure the effective absorption of carbon dioxide by cement during the mixing process.

[0032] (4) The modified carbon-mixed cement material with dual LDH / LDO prepared by the present invention has the advantages of simple preparation method, easy production, convenient use, convenient transportation, strong fluidity, high strength, etc., and has great use value in the field of low-carbon concrete. (5) The present invention proposes a correlation formula between the fluidity of carbon-mixed cement and the amount of carbon dioxide added, and makes a quantitative correction to the mix design of carbon-mixed cement, which has certain research value for the mix design of carbon-mixed cement. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 A schematic diagram of a stirring device according to an embodiment of the present invention;

[0034] Figure 2 This is a physical diagram of a stirring device according to an embodiment of the present invention;

[0035] In the figure: 1. Pressure cylinder; 2. Buffer tank; 3. Air pipe A; 4. Air pipe B; 5. Check valve; 6. Flow meter; 7. Stirring motor; 8. Pressure gauge; 9. Stirring cover; 10. Lock; 11. Stirring barrel; 12. Stirring element. DETAILED DESCRIPTION

[0036] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the technical field without making creative work belong to the scope of protection of the present invention.

[0037] The inventive principle of the present invention is:

[0038] Layered double hydroxide (LDH) has excellent ion exchange and adsorption capacity, and can effectively remove chloride ions, carbonate ions and other factors that have adverse effects on concrete. However, due to the limitation of the specific surface area of ​​LDH, the total amount of ions that it can adsorb is limited, and the synergistic effect with carbon dioxide in carbon-mixed cement is still unclear; LDO is the product obtained by high-temperature calcination of LDH. Compared with LDH, it has a higher specific surface area, so it has a stronger adsorption capacity for ions and can adsorb more harmful ions than LDH; but LDO has stronger alkalinity than LDH, which may reduce the final strength of cement during cement hydration.

[0039] Cobalt-iron-based LDH has better properties than other LDHs. It has better thermal stability and larger crystal interlayer spacing, which helps promote the binding and adsorption of ions. It also has a higher specific surface area and an adsorption capacity that can reach 2 to 3 times that of conventional LDH. It plays an efficient role in the absorption of harmful anions in cement and concrete.

[0040] Carbon-blended cement is a new technology. Compared with traditional carbon curing methods, it has the advantages of low cost and short carbonization time. In addition, due to the in-situ formation of calcium carbonate, its carbonization products can be evenly distributed inside the matrix, effectively filling the microstructure, thereby improving the performance of cement-based materials. However, the introduction of carbon dioxide will cause cement-based materials to harden rapidly, and the fluidity will drop sharply with the increase of carbon dioxide content. This is mainly related to the flocculation structure of hydration products and carbonization products formed on the surface of cement clinker.

[0041] In this specific embodiment, the calcined cobalt-iron layered double hydroxide Co-Fe-LDO is prepared by the following steps:

[0042] Step a1: Take some Co-Fe-LDH and calcine it at 600°C in a muffle furnace for 4 hours with a heating rate of 3°C / min, keep it warm for 8 hours and cool it naturally to obtain calcined cobalt-iron layered double hydroxide Co-Fe-LDO.

[0043] The present invention combines the advantages and disadvantages of LDH and LDO, controls the mixing ratio of LDH and LDO, and develops a Co-Fe-LDH / LDO composite modified carbon mixed cement-based material. In this specific embodiment, the following stirring device is used to stir cement and mix carbon dioxide;

[0044] The stirring device comprises: a stirring tank, a stirring motor 7, a stirring element 12, a flow meter 6, a barometer 8, a buffer tank 2, a pressure cylinder 1, an A air pipe 3 and a B air pipe 4; the stirring tank comprises a stirring barrel 11 and a stirring cover 9, and the stirring barrel 11 has an open top for containing materials;

[0045] The stirring cover 9 is arranged at the top opening of the stirring barrel 11, and the stirring barrel 11 is locked and sealed by a plurality of lock buckles 10 on the side of the stirring barrel 11; the stirring cover 9 has a hole in the middle; the stirring member 12 is arranged in the stirring tank, and one end thereof passes through the middle opening of the stirring cover 9 and is fixedly connected to the output end of the stirring motor 7 arranged on the upper end surface of the stirring cover 9;

[0046] The barometer 8 is used to detect the air pressure in the mixing tank; the pressure cylinder 1 is connected to the buffer tank 2 through the A air pipe 3; the buffer tank 2 is used to convert the carbon dioxide released in the pressure cylinder 1 to normal temperature and pressure, and pass the carbon dioxide into the mixing tank through the B air pipe 4; the flow meter 6 is used to count the amount of carbon dioxide passed into the mixing tank.

[0047] One-way valves are arranged on the A air pipe 3 and the B air pipe 4 to prevent the carbon dioxide gas from flowing in the reverse direction due to changes in air pressure; rubber pads are arranged on the contact surfaces of the stirring cover 9 and the stirring barrel 11 to improve the sealing effect.

[0048] Example 1

[0049] A Co-Fe-LDH / LDO composite modified carbon mixed cement-based material

[0050] Prepare the required mixing water 30%, cobalt-iron layered double hydroxide LDH 3.33%, calcined cobalt-iron layered double hydroxide LDO 1.67%, and cement 65% by weight. The water-cement ratio is 0.46. Weigh 10% of the mixing water by weight, add the required cobalt-iron layered double hydroxide Co-Fe-LDH and calcined cobalt-iron layered double hydroxide Co-Fe-LDO to the mixing water, and perform ultrasonic dispersion for 60s-180s until uniform dispersion to obtain a milky white LDH / LDO suspension; add cement to the mixing bucket and dry mix for 30s, then add the remaining mixing water and LDH / LDO suspension, and continue stirring for 60s-120s until uniform stirring; seal the mixing bucket with a mixing cover, and then pass through a pressure steel pipe. The carbon dioxide is introduced into the mixing tank at a rate of 10L / min through a bottle, and a total of 1% of the total mass of the above materials is introduced. At the same time, the stirring motor is turned on to allow the cement paste to continuously absorb carbon dioxide during the mixing process, that is, carbon-mixed cement paste is formed; the cone mold is placed in the center of the test plate, filled with cement paste, and the mold is quickly lifted after being leveled with a scraper. The diameters of the cement in two vertical directions are recorded and the average values ​​are calculated. The fluidity of the cement is measured to be 26.3cm, the 3d strength is 17.32Mpa, and the 28d strength is 29.24Mpa. According to the formula:

[0051]

[0052] In the formula, M1=0.01, M2=2, M3=0.46, the fluidity of cement can be calculated as Y=26.12cm, which is close to the test result.

[0053] Example 2

[0054] A Co-Fe-LDH / LDO composite modified carbon mixed cement-based material

[0055] Prepare the required mixing water 23.57%, cobalt-iron layered double hydroxide LDH 4%, calcined cobalt-iron layered double hydroxide LDO 1%, and cement 71.43% according to weight percentage. At this time, the water-cement ratio is 0.33. Weigh 10% by weight of mixing water, add the required cobalt-iron layered double hydroxide Co-Fe-LDH and calcined cobalt-iron layered double hydroxide Co-Fe-LDO into the mixing water, and perform ultrasonic dispersion for 60s-180s until uniform dispersion to obtain a milky white LDH / LDO suspension; add cement into a mixing barrel and dry mix for 30s, then add the remaining mixing water and the LDH / LDO suspension, and continue to stir for 60s-120s until uniform stirring; seal the mixing barrel with a mixing cover, then pass carbon dioxide into the stirring device through a pressure cylinder at a rate of 10L / min, and pass 2% of the total mass of the above materials into the stirring device, and turn on the stirring motor at the same time, so that the cement slurry continuously absorbs carbon dioxide during the mixing process, that is, forming a carbon-mixed cement slurry; place a conical mold at the center of a test plate, fill it with cement slurry, level it with a scraper and quickly lift the mold, record the diameters of the cement in two vertical directions, and calculate the average value. The measured fluidity of cement is 22.4cm, the 3d strength is 11.64Mpa, and the 28d strength is 29.65Mpa. According to the formula:

[0056]

[0057] In the formula, M1=0.02, M2=4, M3=0.33, the fluidity of cement can be calculated as Y=22.25cm, which is close to the test result.

[0058] Example 3

[0059] A Co-Fe-LDH / LDO composite modified carbon mixed cement-based material

[0060] Prepare the required mixing water 26.86%, cobalt-iron layered double hydroxide LDH 4.5%, calcined cobalt-iron layered double hydroxide LDO 1.5%, and cement 67.14% according to weight percentage. At this time, the water-cement ratio is 0.40. Weigh 10% by weight of mixing water, add the required cobalt-iron layered double hydroxide Co-Fe-LDH and calcined cobalt-iron layered double hydroxide Co-Fe-LDO into the mixing water, and perform ultrasonic dispersion for 60s-180s until uniform dispersion to obtain a milky white LDH / LDO suspension; add cement into a mixing barrel and dry mix for 30s, then add the remaining mixing water and the LDH / LDO suspension, and continue stirring for 60s-120s until uniform stirring; seal the mixing barrel with a mixing cover, then pass carbon dioxide into the mixing tank through a pressure cylinder at a rate of 10L / min, and a total of 1.5% of the total mass of the above materials is passed in carbon dioxide, and at the same time, turn on the stirring motor to allow the cement slurry to continuously absorb carbon dioxide during the mixing process, that is, to form a carbon-mixed cement slurry; place a conical mold at the center of a test plate, fill it with cement slurry, level it with a scraper and quickly lift the mold, record the diameters of the cement in two vertical directions, and calculate the average value. The measured cement fluidity is 20.1cm, 3d strength is 10.99Mpa, and 28d strength is 36.77Mpa. According to the formula:

[0061]

[0062] In the formula, M1=0.015, M2=3, M3=0.40, the fluidity of cement can be calculated as Y=20.17cm, which is close to the test result.

[0063] Example 4

[0064] A Co-Fe-LDH / LDO composite modified carbon mixed cement-based material

[0065] Prepare the required mixing water 23.57%, cobalt-iron layered double hydroxide LDH 3.33%, calcined cobalt-iron layered double hydroxide LDO 1.67%, and cement 71.43% according to weight percentage. At this time, the water-cement ratio is 0.33. Weigh 10% by weight of mixing water, add the required cobalt-iron layered double hydroxide Co-Fe-LDH and calcined cobalt-iron layered double hydroxide Co-Fe-LDO into the mixing water, and perform ultrasonic dispersion for 60s-180s until the dispersion is uniform, thereby obtaining a milky white LDH / LDO suspension; add cement into a mixing barrel and dry mix for 30s, then add the remaining mixing water and the LDH / LDO suspension, and continue to stir for 60s-120s until the mixing is uniform; seal the mixing barrel with a mixing cover, then pass carbon dioxide into the mixing tank through a pressure cylinder at a rate of 10L / min, and pass 1% of the total mass of the above materials into the mixing tank, and turn on the stirring motor at the same time, so that the cement slurry continuously absorbs carbon dioxide during the mixing process, that is, forming a carbon-mixed cement slurry; place a conical mold at the center of a test plate, fill it with cement slurry, level it with a scraper, and quickly lift the mold, record the diameters of the cement in two vertical directions, and calculate the average value. The measured fluidity of cement is 30.04cm, the 3d strength is 12.17Mpa, and the 28d strength is 33.87Mpa. According to the formula:

[0066]

[0067] In the formula, M1=0.01, M2=2, M3=0.33, the fluidity of cement can be calculated as Y=30.27cm, which is close to the test result.

[0068] Example 5

[0069] A Co-Fe-LDH / LDO composite modified carbon mixed cement-based material

[0070] Prepare the required mixing water 30%, cobalt-iron layered double hydroxide LDH 4%, calcined cobalt-iron layered double hydroxide LDO 1%, and cement 65% according to weight percentage. At this time, the water-cement ratio is 0.46. Weigh 10% by weight of mixing water, add the required cobalt-iron layered double hydroxide Co-Fe-LDH and calcined cobalt-iron layered double hydroxide Co-Fe-LDO into the mixing water, and perform ultrasonic dispersion for 60s-180s until the dispersion is uniform, thereby obtaining a milky white LDH / LDO suspension; add cement into a mixing barrel and dry mix for 30s, then add the remaining mixing water and the LDH / LDO suspension, and continue to stir for 60s-120s until the mixing is uniform; seal the mixing barrel with a mixing cover, then pass carbon dioxide into the mixing tank through a pressure cylinder at a rate of 10L / min, and pass 1% of the total mass of the above materials into the mixing tank, and turn on the stirring motor at the same time, so that the cement slurry continuously absorbs carbon dioxide during the mixing process, that is, forming a carbon-mixed cement slurry; place a conical mold at the center of a test plate, fill it with cement slurry, level it with a scraper, and quickly lift the mold, record the diameters of the cement in two vertical directions, and calculate the average value. The measured cement fluidity is 29.53cm, 3d strength is 9.47Mpa, and 28d strength is 28.63Mpa. According to the formula:

[0071]

[0072] In the formula, M1=0.01, M2=4, M3=0.46, the fluidity of cement can be calculated as Y=29.62cm, which is close to the test result.

[0073] Example 6

[0074] A Co-Fe-LDH / LDO composite modified carbon mixed cement-based material

[0075] Prepare the required mixing water 23.57%, cobalt-iron layered double hydroxide LDH 3.33%, calcined cobalt-iron layered double hydroxide LDO 1.67%, and cement 71.43% according to weight percentage. At this time, the water-cement ratio is 0.33. Weigh 10% by weight of mixing water, add the required cobalt-iron layered double hydroxide Co-Fe-LDH and calcined cobalt-iron layered double hydroxide Co-Fe-LDO into the mixing water, and perform ultrasonic dispersion for 60s-180s until the dispersion is uniform, thereby obtaining a milky white LDH / LDO suspension; add cement into a mixing barrel and dry mix for 30s, then add the remaining mixing water and the LDH / LDO suspension, and continue to stir for 60s-120s until the mixing is uniform; seal the mixing barrel with a mixing cover, then pass carbon dioxide into the mixing tank through a pressure cylinder at a rate of 10L / min, and pass 2% of the total mass of the above materials into the mixing tank, and turn on the stirring motor at the same time, so that the cement slurry continuously absorbs carbon dioxide during the mixing process, that is, forming a carbon-mixed cement slurry; place a conical mold at the center of a test plate, fill it with cement slurry, level it with a scraper, and quickly lift the mold, record the diameters of the cement in two vertical directions, and calculate the average value. The measured fluidity of cement is 16.1cm, the 3d strength is 13.29Mpa, and the 28d strength is 31.57Mpa. According to the formula:

[0076]

[0077] In the formula, M1=0.02, M2=2, M3=0.33, the fluidity of cement can be calculated as Y=15.25cm, which is close to the test result.

[0078] Example 7

[0079] A Co-Fe-LDH / LDO composite modified carbon mixed cement-based material

[0080] Prepare the required mixing water 30%, cobalt-iron layered double hydroxide LDH 4%, calcined cobalt-iron layered double hydroxide LDO 1%, and cement 65% according to weight percentage. At this time, the water-cement ratio is 0.46. Weigh 10% by weight of mixing water, add the required cobalt-iron layered double hydroxide Co-Fe-LDH and calcined cobalt-iron layered double hydroxide Co-Fe-LDO into the mixing water, and perform ultrasonic dispersion for 60s-180s until the dispersion is uniform, thereby obtaining a milky white LDH / LDO suspension; add cement into a mixing barrel and dry mix for 30s, then add the remaining mixing water and the LDH / LDO suspension, and continue to stir for 60s-120s until the mixing is uniform; seal the mixing barrel with a mixing cover, then pass carbon dioxide into the mixing tank through a pressure cylinder at a rate of 10L / min, and pass 2% of the total mass of the above materials into the mixing tank, and turn on the stirring motor at the same time, so that the cement slurry continuously absorbs carbon dioxide during the mixing process, that is, forming a carbon-mixed cement slurry; place a conical mold at the center of a test plate, fill it with cement slurry, level it with a scraper, and quickly lift the mold, record the diameters of the cement in two vertical directions, and calculate the average value. The measured fluidity of cement is 19.5cm, the 3d strength is 11.53Mpa, and the 28d strength is 31.21Mpa. According to the formula:

[0081]

[0082] In the formula, M1=0.02, M2=4, M3=0.46, the fluidity of cement can be calculated as Y=19.32cm, which is close to the test result.

[0083] Example 8

[0084] A Co-Fe-LDH / LDO composite modified carbon mixed cement-based material

[0085] Prepare the required mixing water 30%, cobalt-iron layered double hydroxide LDH 3.33%, calcined cobalt-iron layered double hydroxide LDO 1.67%, and cement 65% according to weight percentage. At this time, the water-cement ratio is 0.46. Weigh 10% of mixing water by weight, add the required cobalt-iron layered double hydroxide Co-Fe-LDH and calcined cobalt-iron layered double hydroxide Co-Fe-LDO into the mixing water, and perform ultrasonic dispersion for 60s-180s until the dispersion is uniform and the solution is a milky white suspension; add cement into a mixing barrel and dry mix for 30s, then add mixing water and LDH / LDO suspension, and continue stirring for 60s-120s until the mixing is uniform; seal the mixing barrel with a mixing cover, then pass carbon dioxide into the mixing tank through a pressure cylinder at a rate of 10L / min, and a total of 2% of the total mass of the above materials is passed in carbon dioxide, and at the same time turn on the stirring motor to allow the cement slurry to continuously absorb carbon dioxide during the mixing process, that is, to form a carbon-mixed cement slurry; place a conical mold at the center of a test plate, fill it with cement slurry, level it with a scraper and quickly lift the mold, record the diameters of the cement in two vertical directions, and calculate the average value. The measured fluidity of cement is 14.21cm, the 3d strength is 14.17Mpa, and the 28d strength is 35.41Mpa. According to the formula:

[0086]

[0087] In the formula, M1=0.02, M2=2, M3=0.46, the fluidity of cement can be calculated as Y=12.32cm, which is close to the test result.

[0088] Comparative Example:

[0089] Weigh the mixing water and cement of the same mass as Example 8, but do not add cobalt-iron layered double metal hydroxide LDH and calcined cobalt-iron layered double metal hydroxide LDO, and the water-cement ratio is 0.46. Add cement to the mixing barrel and dry mix for 30s, then add mixing water, and continue stirring for 60s-120s until it is evenly stirred; seal the mixing barrel with a stirring cover, then pass carbon dioxide into the mixing tank at a rate of 10L / min through a pressure cylinder, and pass a total of 2% of the total mass of the above materials into the carbon dioxide, and turn on the stirring motor at the same time, so that the cement slurry continuously absorbs carbon dioxide during the mixing process, that is, forming carbon mixed cement slurry; place the conical mold in the center of the test plate, fill it with cement slurry, and quickly lift the mold after leveling it with a scraper, record the diameters of the cement in two vertical directions, and calculate the average value. The fluidity of the cement was measured to be 10.25cm, the 3d strength was 11.28Mpa, and the 28d strength was 30.66Mpa. It can be seen that the fluidity and strength of cement without LDH / LDO addition are reduced.

[0090] A modified carbon-mixed cement-based material doped with Co-Fe-LDH / LDO of the present invention can effectively improve the problems of poor fluidity and low strength of carbon-mixed cement. The modified carbon-mixed cement doped with LDH / LDO prepared by the present invention has significantly improved early and late strengths, and significantly enhanced fluidity; the early 3d strength reaches a maximum of 17.32Mpa (Example 1), the late 28d strength reaches a maximum of 36.77Mpa (Example 3), and the fluidity reaches a maximum of 30.04cm (Example 4). The double-doped cobalt-iron layered double metal hydroxide Co-Fe-LDH and the calcined cobalt-iron layered double metal hydroxide Co-Fe-LDO overcome the shortcomings of low specific surface area and low adsorption of conventional LDH, and further improve the performance of cement. The carbon dioxide adsorption effect is effectively controlled by three parameters: water-cement ratio, LDH / LDO ratio, and CO2 dosage, forming an optimal design ratio method for cement fluidity and carbon dioxide adsorption. The relationship between cement fluidity and the three parameters of water-cement ratio, carbon dioxide adsorption and LDH / LDO ratio is fitted using a formula, which helps to achieve dual optimization of carbon fixation and working performance of carbon-mixed cement.

Claims

1. A modified carbon mixed cement-based material doped with Co-Fe-LDH / LDO, characterized in that: The mixture comprises the following components by weight: 350-400 parts of cement, 200-250 parts of mixing water, 3-4 parts of cobalt-iron layered double hydroxide Co-Fe-LDH, 2-3 parts of calcined cobalt-iron layered double hydroxide Co-Fe-LDO, and 2-8 parts of carbon dioxide; Wherein, the calcined cobalt-iron layered double hydroxide Co-Fe-LDO is prepared by the following steps: Step a1: Take some Co-Fe-LDH and calcine it at 600° C. in a muffle furnace with a heating rate of 3° C. / min. After keeping warm, cool it naturally to obtain calcined cobalt-iron layered double hydroxide Co-Fe-LDO.

2. The modified carbon mixed cement-based material doped with Co-Fe-LDH / LDO according to claim 1, characterized in that: The cement is ordinary Portland cement, and the model is P·O 42.

5.

3. The modified carbon mixed cement-based material doped with Co-Fe-LDH / LDO according to claim 1, characterized in that: The particle size of the cobalt-iron layered double hydroxide Co-Fe-LDH is 0.5-2.0 microns, and the specific surface density is 0.2-0.4 g / mol.

4. A method for preparing a modified carbon-mixed cement-based material doped with Co-Fe-LDH / LDO, for preparing the modified carbon-mixed cement-based material doped with Co-Fe-LDH / LDO as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: Step 1, weighing 100-120 parts of mixing water from the 200-250 parts of mixing water by mass, adding the Co-Fe-LDH and the Co-Fe-LDO to the weighed mixing water, and performing ultrasonic dispersion until the dispersion is uniform to obtain a milky white LDH / LDO suspension; Step 2: Add the cement into a stirring device for dry mixing, then add the remaining mixing water and LDH / LDO suspension, and continue stirring until the mixture is uniform to obtain cement slurry; Step 3, introducing the carbon dioxide into the cement paste at a rate of 8 to 10 L / min, and continuing to stir, so that the cement paste continuously absorbs carbon dioxide during the mixing process, and finally obtaining carbon-mixed cement paste; Step 4: pour the carbon-mixed cement slurry into a mold, scrape off excess slurry, and demould after curing in a curing room for 7 days to obtain a modified carbon-mixed cement-based material doped with Co-Fe-LDH / LDO.

5. The method for preparing a carbon-mixed cement-based material doped with Co-Fe-LDH according to claim 4, characterized in that: In step 1, the ultrasonic dispersion time is 60s-180s, in step 2, the dry mixing time is 30s, and the remaining mixing water and LDH / LDO suspension are continued to be stirred for 60s-120s.

6. The method for preparing a carbon-mixed cement-based material doped with Co-Fe-LDH according to claim 4, characterized in that: During the curing process, the temperature is maintained at 20±2° C. and the relative humidity is maintained at above 95%.

7. The method for preparing a carbon-mixed cement-based material doped with Co-Fe-LDH according to claim 4, characterized in that: The stirring device comprises: a stirring tank, a stirring motor (7), a stirring element (12), a flow meter (6), a pressure gauge (8), a buffer tank (2), a pressure cylinder (1), an A air pipe (3) and a B air pipe (4); the stirring tank comprises a stirring barrel (11) and a stirring cover (9); the stirring barrel (11) has an opening at the top for containing materials; The stirring cover (9) is arranged at the top opening of the stirring barrel (11), and the stirring barrel (11) is locked and sealed by a plurality of lock buckles (10) on the side of the stirring barrel (11); a hole is opened in the middle of the stirring cover (9); the stirring element (12) is arranged in the stirring tank, and one end of the stirring element (12) passes through the middle opening of the stirring cover (9) and is fixedly connected to the output end of the stirring motor (7) arranged on the upper end surface of the stirring cover (9); The barometer (8) is used to detect the air pressure in the stirring tank; the pressure cylinder (1) is connected to the buffer tank (2) via the A air pipe (3); the buffer tank (2) is used to convert the carbon dioxide released from the pressure cylinder (1) to normal temperature and pressure, and to pass the carbon dioxide into the stirring tank via the B air pipe (4); the flow meter (6) is used to count the amount of carbon dioxide passed into the stirring tank.

8. The method for preparing a carbon-mixed cement-based material doped with Co-Fe-LDH according to claim 7, characterized in that: One-way valves are provided on the A air pipe (3) and the B air pipe (4) to prevent the carbon dioxide gas from flowing in the opposite direction due to changes in air pressure; and rubber pads are provided on the contact surfaces of the stirring cover (9) and the stirring barrel (11) to improve the sealing effect.

9. A method for correcting the raw material ratio of a modified carbon mixed cement-based material doped with Co-Fe-LDH / LDO, used for correcting the raw material ratio of the modified carbon mixed cement-based material doped with Co-Fe-LDH / LDO as claimed in any one of claims 1 to 3, characterized in that: The steps include: Step 1: Preliminary mix design of the water-cement ratio and the mass ratio of Co-Fe-LDH to Co-Fe-LDO m(LDH) / m(LDO) is performed according to the required carbon dioxide content; Step 2: According to the Levenberg-Marquardt algorithm and the Spearman correlation coefficient algorithm, the carbon dioxide content is recorded as M1, m(LDH) / m(LDO) is recorded as M2, and the water-cement ratio is recorded as M3. M1, M2 and M3 are fitted with functions about the cement fluidity Y to obtain the following calculation formula: Step three, according to the required cement fluidity Y and the calculation formula obtained in step two, the values ​​of M2 and M3 in the formula are changed to adjust the maximum amount of carbon dioxide that can be adsorbed. According to the values ​​of M2 and M3, the mix ratio in step one is corrected to obtain the final raw material mix ratio of modified carbon mixed cement-based materials.

Citation Information

Patent Citations

  • Preparation process of modified cement and early-strength ultra-high performance concrete thereof

    CN115784647A

  • Chemical-erosion-resisting, high-strength and high-toughness concrete and preparation method thereof

    CN107032673A

  • NiFe-LDH cement-based composite wave-absorbing material and preparation method thereof

    CN112745084A

  • Hybrid material based on layered double hydroxide-saccharomyces cerevisiae as well as preparation method and application of hybrid material

    CN114345377A

  • Unfired fly ash ceramsite as well as preparation method and application thereof

    CN118255554A